2022
DOI: 10.3847/1538-4357/aca403
|View full text |Cite
|
Sign up to set email alerts
|

Extreme Nature of Four Blue-excess Dust-obscured Galaxies Revealed by Optical Spectroscopy

Abstract: We report optical spectroscopic observations of four blue-excess dust-obscured galaxies (BluDOGs) identified by the Subaru Hyper Suprime-Cam. BluDOGs are a subclass of dust-obscured galaxies (DOGs; defined with the extremely red color (i − [22])AB ≥ 7.0; Toba et al., showing a significant flux excess in the optical g and r bands over the power-law fits to the fluxes at the longer wavelengths. Noboriguchi et al. have suggested that BluDOGs may correspond to the blowing-out phase involved in a gas-rich major-mer… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 100 publications
0
13
0
Order By: Relevance
“…In this Letter, we use the JWST-ERO samples taken from Barro et al (2023) and Matthee et al (2023) and the BluDOG sample taken from Noboriguchi et al (2022). Barro et al (2023) selected 37 JWST-EROs in CEERS fields (Finkelstein et al 2023) based on the single color criterion (F277W − F444W) AB >1.5.…”
Section: Samplementioning
confidence: 99%
See 4 more Smart Citations
“…In this Letter, we use the JWST-ERO samples taken from Barro et al (2023) and Matthee et al (2023) and the BluDOG sample taken from Noboriguchi et al (2022). Barro et al (2023) selected 37 JWST-EROs in CEERS fields (Finkelstein et al 2023) based on the single color criterion (F277W − F444W) AB >1.5.…”
Section: Samplementioning
confidence: 99%
“…However, Noboriguchi et al (2019) found eight DOGs with blue excess in optical bands (blueexcess DOGs; BluDOGs) using an observed-frame optical slope (α opt < 0.4, where α opt denotes the observed-frame optical spectral index of the power law fitted to the HSC g-, r-, i-, z-, and y-band fluxes, f opt l µ n a ). After spectroscopic follow-up observations, Noboriguchi et al (2022) reported that BluDOGs are broad-line AGNs at 2 < z < 3 and the origin of the blue-excess are blue continuum and large equivalent widths (EWs) of the broad emission lines. In addition, C IV lines exhibit a blue tail, suggesting that BluDOGs have nuclear outflows (Noboriguchi et al 2022).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations